Peran Komunikasi Organisasi dalam Meningkatkan Eksistensi Surabaya Next Leader - Prastiti, Tiara; Abdau, Muhammad Sobari; Safura, Aqilah Nur; Pertiwi, Afanda Putri; Wibowo, M. Akbar; Zuhri, Saifuddin (Universitas Pahlawan Tuanku Tambusai, 2024)
Jurnal dengan judul